The Impact of Social Media on the Cultural Identity of Bahraini Youth: A Field Study (The International Journal of Educational Sciences and Arts, 2025)
This study aims to demonstrate the impact of social media on the cultural identity of young people, especially university students. It examines the most important social and psychological motivations that drive their use of these sites, particularly Facebook and Instagram, as they are the most widely used in Bahrain. The gratifications achieved through this virtual interaction are reflected in the individual's cultural identity, whether in terms of language, religion, or the gains of a shared national history. This impact, as well as social relations, has been clearly and rapidly evident in Bahraini society. We will analyze all of this quantitatively and qualitatively to demonstrate the true extent of the influence of these social networks on cultural identity. The study's problem was to measure the role played by social media in strengthening cultural identity. The study relied on cultural identity theory, which is considered one of the most important theories contributing to understanding the depth of cultural communication in our current era. It focuses on a deep understanding of culture and how it shapes individual and collective identity. This theory is based on the idea that identity is not a fixed entity, but rather is variable and intertwined due to the various cultural influences to which individuals are exposed within their community and beyond. Regarding the methodology used in the study, it falls within the category of descriptive research. The study relied on data collection tools: observation and questionnaires as the primary tools, especially since they allow for in-depth collection of information about the respondents. Observation: One of the most important tools used in data collection, as it allows the researcher to gather information and facts, is the questionnaire. This questionnaire consists of a set of carefully and precisely designed questions that are sequential and clearly worded.The study reached several conclusions, the most important of which is that cultural identity is actually and profoundly affected by the use of social media in terms of satisfaction and the needs it fulfills. We find that Bahraini youth in general, and students in particular, are facing a kind of challenge, trying to preserve their identity and cultural heritage on the one hand, and keeping pace with the developments and progress witnessed by the world in light of the widespread use of social media, interaction through them, and the rapid exchange of cultures, transcending geographical boundaries.
Keywords: Social Media; Cultural Identity; Youth; Bahrain